Розробка контактних матеріалів на основі міді та дослідження контактного опору електромагнітних пускачів - Коробський, В. В.; Бурла, А. В. (Енергетика і автоматика, 2017)
UDK 621.3.064.035/620.268 DEVELOPMENT OF CONTACT MATERIALS BASED ON COPPER AND INVESTIGATION OF CONTACT RESISTANCE OF ELECTROMAGNETIC STARTERS V.V. Korobskyy, A.V. Burla Abstract. Features of materials for contacts of electromagnetic starters, as well as properties and composition of the developed composite environmentally safe materials for contactor systems of starters are given. The results of studies of the contact resistance of the PML-1100 starter with serial and experimental material on the number of switching cycles are presented. The aim of the work is to create an environmentally friendly contact material for starters working in electrical installations of agriculture, while achieving a low cost with a specified level of reliability for the transient resistance. Materials and methods of research. In order to reduce the time and means of testing, a single-stage control is used, in which one sample is tested (according to the results of the test, a decision is made about compliance with reliability requirements). Taking into account the service functions of the electromagnetic starters used in the electrical installations of agriculture with currents of 10 ... 25 A, we use the prototype for creating research contact materials for the known sintered contact materials based on copper KMK-B00 (99.95% Cu), KMK-B10 (97% Cu + 3% C) and KMК-B11 (95% Cu + 5% C). The transient resistance of serial and experimental contact pairs is determined by the voltmeter-ammeter method with a total number of switching cycles of 300 thousand. The processing of the results of the study was carried out using mathematical statistics using the "Statistika" software package (version 10.0). Conclusions and prospects. The conducted studies showed that, in general, the resistivity of composite copper-based contact materials is comparable to the resistivity of КMК-A10m, KMK-A40 silver-based kontact materials. The experimental dependences of the transition contact resistance on the number of switching cycles are approximated by a polynomial of the first degree. Dynamics increase in the value of the transient resistance of the investigated contacts is lower (in 2..3.5 times) and the resistance grows more slowly, compared with the serial ones, for which the growth of the resistance value is fixed by 5 ... 7 times, when the starters operate in a medium with chemically active additives. Key words: contact material, electromagnetic starter, transient resistance, compositional material components, electrical conductivity. Introduction. Starters manufactured by the domestic industry, according to their technical parameters, basically correspond to the modern world level, but taking into account the trends and dynamics of the development of electromagnetic actuators abroad, there may be a lag behind a number of parameters from samples of foreign firms. Analysis of recent researches and publications. Requirements for electromagnetic actuators are formulated in the international standard IEC 60947-4-1. Material and composition of contacts is determined by the category of application, the most common of which are the categories AC-3 and AC-4. The materials of contacts of electromagnetic actuators are put forward the following requirements: high mechanical wear resistance; high electrical wear resistance; high resistance to welding; high electrical conductivity; high thermal conductivity; low and stable transient resistance; low propensity to interact with chemically active impurities of the environment of the agrarian sector (hydrogen sulfide, carbon dioxide, ammonia, sulfur dioxide, etc.); ensuring reliable fastening to the contact holder; low cost at a given level of reliability. It is practically impossible to pick up a universal material that would meet all the named requirements, therefore, depending on the functional purpose of the contact node, it is necessary to make a compromise solution. The purpose of the study is to create an environmentally friendly contact material for starters operating in electrical installations of agriculture, with the achievement of low cost with a given level of reliability regarding transient resistance. Materials and methods of research. One-stage control, in which one sample is tested, is used (based on the results of the test, they decide on compliance with the requirements of reliability). Taking into account the official functions of electromagnetic actuators used in electrical installations of agriculture with currents 10 ... 25A, we will take prototype for creation of research contact materials known sintered contact materials on the basis of copper type KMK-B. The disadvantage of these materials is low electrospray resistance, instability of contact resistance during operation. The values of the voltage drop for serial contacts and the experimental ones were processed using the methods of mathematical statistics using the program "Statistics" (version 10.0). Transient resistance of serial and experimental contact pairs was determined by the method of voltmeter-ammeter. Results. To improve the electro-erosive stability and maintain a stable contact resistance to the materials mentioned above, we introduced impurities, which allowed the creation and the patenting of new composite materials: 1) Cu + (10-15%) Mo + (2-3%) MoO3 + (1-3%) C + (0.8-1.0%) Ni. The introduction of a molybdenum that does not interact with the medium in a solid or liquid state greatly increases firmness, firmness and ductility. To stabilize the contact resistance, alloying impurities of molybdenum trioxide MoO3 and graphite C. were introduced. Simultaneous introduction of Mo, MoO3, Ni, C gives the material the necessary service properties, which are necessary for contact materials of starter actuators. The mechanism of forming the composition from Mo and Cu is determined by processes that pass on the surfaces of the phase separation, namely, wetting and adhesion. 2. Cu + (5.0-10%) Cr + (1.0-3.0%) TiB2 + (2.0-3.0%) Nb + (1.0-2.0%) C + (0.5- 0.7%) Zr. The impurity of chromium allowed to disperse the material due to the high hardness of Cr, which exceeds the hardness of copper almost three times. The chrome under the action of the arc, which occurs when switching current, is easily oxidized to Cr2O3, which increases the resistance of the arc. As a result, the current in the arc decreases, the burning time of the arc is reduced, which leads to a decrease in erosion. Copper is less oxidized due to the absorption of chromium by oxygen, which stabilizes contact resistance. Niobium particles on the working surface of the contacts create a large temperature gradient at the boundary of the Nb- Cu phases. Conclusion Experimental dependences of the transient contact resistance on the number of switching cycles are approximated by the polynomial of the first degree. The dynamics of the increase in the value of the transient resistance of the experimental contacts is lower (in 2..3 times) and the resistance increases more slowly, unlike the serial ones, for which the increase of the resistance value is fixed in 5 ... 7 times, with the operation of triggers in a medium with a chemically active admixtures